Experimental energy-exergy performance and kinetics analyses of compact dual-mode heat pump drying of food chips - Singh A.; Sarkar J.; Sahoo R.R. (My University, 2025)
Batch-type heat pump dryer operating in both closed and open-cycle modes with improved tray design is developed to investigate the energetic and exergetic performances, and drying kinetics of banana and potato chips. Effects of drying time on various performances and drying kinetic parameters are presented. Coefficient of performance of heat pump as well as whole system is higher for open-cycle mode. Higher specific moisture extraction rate is obtained as 1.248 kg/kWh for closed cycle drying of banana chips. Drying efficiency is also found higher for the closed cycle. The specific energy consumption is lower (0.8 kWh/kg) in closed system drying for banana. Total exergy destruction is found higher for the closed system. Mass transfer coefficient and moisture diffusivity are better for the closed system. On the basis of studied performance parameters, the closed system drying is found better than the open system drying in humid and hot ambient conditions. Practical Applications: This study develops a heat pump dryer (HPD) operated with both closed and open-cycle modes, which can control the air recirculation to provide optimum main drying parameters to get the best drying performance. The novelty of this study is twofold: controlling of air recirculation to get optimum condition and improved design of trays in drying cabinet for best possible air distribution to get maximum SMER (the obtained SMER value is more than the reported SMER values of other developed prototypes available in the literature). The results have been evaluated to provide better information about the benefits of varying air recirculation in the HPD system. Drying kinetic has also been determined experimentally, which will be helpful for modeling potato and banana drying. This study will help to develop commercial HPD operated in closed/open mode depending on environmental conditions for food chips drying. © 2020 Wiley Periodicals, Inc.